Melon fruit quality front mildew incidence and management of nitrogen and potassium topdressing - Santos, Gil Rodrigues; Bonifacio, Aurenivia; Rodrigues, Artenisa Cerqueira; Dalcin, Mateus Sunti; Sarmento, Renato Almeida; Nascimento, Ildon Rodrigues (Comunicata Scientiae, 2018)
This work aimed to evaluate the application effect of different dosages of nitrogen and potassium topdressing on mildew severity and on yield and fruit quality of melon. The three cultivars, Jangada, Gaucho Casca de Carvalho and Gaucho Redondo Cone Sul were evaluated in Cerrado (savannah) and floodplain areas. At 34 days after sowing (DAS) the topdressing treatments with different dosages of nitrogen and potassium were applied. The mildew severity estimation started at 56 DAS and was performed in five-days intervals until the harvesting of the fruits. The yield and physicochemical characteristics of the collected fruits were evaluated at harvest. There was no significative interaction among nitrogen and potassium topdressing, the cultivars and cultivated areas. However, there was significative differences when the factors were analyzed in separate. The cultivar Gaucho Redondo Cone Sul showed a significant linear increase in the area under the disease progress curve and higher productivity on cerrado compared to the remaining cultivars. The cultivar Gaucho Casca de Carvalho produced heavier and with higher °Brix fruits on cerrado. It is possible to conclude that the applied topdressings did not reduce the mildew severity in all tested cultivars, but they increased the yield in the floodplain area without modifying the physicochemical characteristics of the pulp on the evaluated melon fruits.